Acoustic emission in compressed Mg-Li and Al alloys processed by ECAP, HPT and ARB methods - Andrzej Pawełek; Andrzej Piątkowski; Jan Kuśnierz; Joanna Bogucka; Zdzisław Jasieński; Zbigniew Ranachowski; Przemysław Ranachowski; Jarosław Mizera; Stanislav Kúdela; Stanislaw Kúdela Jr. (Archives of Acoustics, 2014)
In the paper there are presented the results of investigations of the relations between acoustic emission (AE) and the plastic strain mechanisms during channel-die compression of materials, based on both Mg-Li and Al alloys, having ultra fine-grained (UFG) or nanocrystalline structure obtained using the technique of equal channel (of both quadratic and circular section) angular pressing (ECAP) as well as the technique of high pressure torsion (HPT). Also the AE in compression and tensile tests of UFG (nanocrystalline) Al alloys obtained by accumulative roll-bonding (ARB) method have been investigated. The results obtained using a new generation AE analyzer are compared with those obtained for similar materials but not subjected to ECAP, HPT and ARB processing. Moreover, the wavelet analysis of the detected AE signals based on the acoustic maps (acoustograms) and spectral characteristics has been carried out and the AE behaviour is discussed in the dislocation aspects of both plastic strain mechanisms and possible superplastic flow in UFG or nanocrystalline materials.